Losing Sense of Self and Surroundings: Hematopoietic Stem Cell Aging and Leukemic Transformation - Verovskaya, Evgenia V. (Trends Mol Med, 2019)
Aging leads to functional decline of the hematopoietic system, manifested by an increased incidence of hematological disease in the elderly. Deterioration of hematopoietic integrity with age originates in part from the degraded functionality of hematopoietic stem cells (HSCs). Here, we review recent findings identifying changes in metabolic programs and loss of epigenetic identity as major drivers of old HSC dysfunction and their role in promoting leukemia onset in the context of age-related clonal hematopoiesis (ARCH). We discuss how inflammatory and growth signals from the aged bone marrow (BM) microenvironment contribute to cell-intrinsic HSC aging phenotypes and favor leukemia development. Finally, we address how metabolic, epigenetic, and inflammatory pathways could be targeted to enhance old HSC fitness and prevent leukemic transformation.